2017
DOI: 10.1080/23744235.2017.1292046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcome and clinical characteristics of bacteremia caused by methicillin-resistant, penicillin-resistant and penicillin-susceptibleStaphylococcus aureusstrains

Abstract: MRSA bacteremia was associated with poorer outcome than either PRSA or PSSA bacteremia. We corroborated several risk factors found in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Active drug efflux systems play a role in resistance to multiple drugs (Costa et al, 2018). There are three types of multidrugpumping proteins present on the Staphylococcus aureus cell membrane: QacA, NorA, and Smr (Foster, 2016;Jang, 2016). Noguchi et al considered QacA to be an important factor in MRSA (Noguchi et al, 2005;Nakaminami et al, 2019).…”
Section: Efflux Systemsmentioning
confidence: 99%
“…Active drug efflux systems play a role in resistance to multiple drugs (Costa et al, 2018). There are three types of multidrugpumping proteins present on the Staphylococcus aureus cell membrane: QacA, NorA, and Smr (Foster, 2016;Jang, 2016). Noguchi et al considered QacA to be an important factor in MRSA (Noguchi et al, 2005;Nakaminami et al, 2019).…”
Section: Efflux Systemsmentioning
confidence: 99%
“…In recent years, the prevalence of MRSA is rising. The infection due to the MRSA strains has a higher mortality rate than the infection caused by the methicillin-sensitive Staphylococcus aureus (MSSA) strains, which brings great difficulty to treatment[3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Our study disclosed, however, that MRSA was a significant factor in morbidity. Jokinen and others [27], as well, described that MRSA predicted worse outcomes than did methicillin-susceptible S. aureus. Ohashi et al [28] showed, however, that pharmacists' intervention in MRSA bacteremia improved the survival of sepsis patients.…”
Section: Discussionmentioning
confidence: 94%